The 5th wave ebook - Yancey, Rick (The 5th Wave, 2013)
#1 NEW YORK TIMES BESTSELLER • A gripping tale of catastrophic loss, unthinkable odds, and unflinching courage in the first book in epic series from award-winning author Rick Yancey.  "Remarkable, not-to-be-missed-under-any-circumstances."— Entertainment Weekly "A modern sci-fi masterpiece . . ."—USAToday.com After the 1st wave, only darkness remains. After the 2nd, only the lucky escape. And after the 3rd, only the un lucky survive. After the 4th wave, only one rule applies: trust no one. Now, it's the dawn of the 5th wave, and on a lonely stretch of highway, Cassie runs from Them. The beings who only look human, who roam the countryside killing anyone they see. Who have scattered Earth's last survivors. To stay alone is to stay alive, Cassie believes, until she meets Evan Walker. Beguiling and mysterious, Evan Walker may be Cassie's only hope for rescuing her brother—or even saving herself. But Cassie must choose: between trust and despair, between defiance and surrender, between life and death. To give up or to get up. "Wildly entertaining . . . I couldn't turn the pages fast enough."—Justin Cronin, The New York Times Book Review A USA Today bestseller • Winner of the 2014 Red House Children's Book Award • 2014 Children’s Choice Book Awards Finalist for Teen Book of the Year • A YALSA 2014 Best Fiction for Young Adults • A YALSA 2014 Quick Picks for Reluctant Young Readers • A Booklist 2014 Best Fiction for Young Adults • A VOYA 2013 Perfect Ten